Danlou tablet inhibits the inflammatory reaction of high-fat diet-induced atherosclerosis in ApoE knockout mice with myocardial ischemia via the NF-κB signaling pathway. (5th December 2020) - Gao, Shan; Xue, Xiaoxue; Yin, Jia; Gao, Lina; Li, Zhu; Li, Lin; Gao, Shuming; Wang, Shuo; Liang, Ru; Xu, Yilan; Yu, Chunquan; Zhu, Yan
Abstract: Ethnopharmacological relevance: Danlou tablet (DLT), a traditional herbal formula, has been used to treat chest discomfort (coronary atherosclerosis) in China. Although the anti-inflammatory activities of DLT have been proposed previously, the mechanisms of DLT in treating atherosclerosis with myocardial ischemia (AWMI) remain unknown. Aim of the study: Atherosclerosis can result in heart disease caused by stenosis or occlusion of the lumen, resulting in myocardial ischemia, hypoxia, or necrosis. In recent years, changes in people's diets, increased stress, and secondary fatigue and obesity etc. have resulted in increases in the number of patients with atherosclerosis. In cases where the condition has further developed, patients may suffer from myocardial ischemia, hypoxia, or necrosis. Many traditional Chinese medicine compounds have been prescribed for the treatment of AWMI. DLT has been used to treat chest discomfort (coronary atherosclerosis) in China. Based on previous research, the aim of this study was to further investigate the effect of DLT on AWMI, and describe the underlying mechanisms. Materials and methods: To achieve this, an animal model of AWMI was established using apolipoprotein E (ApoE −/- ) mice fed a high fat diet combined with isoprenaline (ISO) injection. For comparison, mouse models of only atherosclerosis and only myocardial ischemia were included. In the treatment groups, mice were treated daily with DLT at 700 mg/kg for four weeks. Echocardiographic evaluation, hematoxylin and eosin (H&E) staining, oil red O staining, ELISAs, Western blots, and immunohistochemical analyses were subsequently used to investigate the mechanism of DLT based on the NF-κB signaling pathway. Results: The results indicate that the use of DLT is effective, to varying degrees, for the treatment of atherosclerosis, myocardial ischemia, and AWMI in mice. After DLT treatment, the left ventricular structure and morphology of the mice, the histopathology of cardiac tissue, and atherosclerotic plaques in the aortas all improved to varying degrees. DLT could play a therapeutic role by regulating the NF-κB signaling pathway related to inflammatory factors, including TNF-α, IL-6, IL-1β, IL-8, MMP-1 and MMP-2, as well as protein expression of NF-κB p-50 and IκB-α, and positive cell expression of NF-κB p-50, IκB-α and phospho-NF-κB p-50 in the model mice. Conclusion: These preliminary results indicate that the therapeutic efficacy of DLT on high-fat diet-induced atherosclerosis in ApoE −/- mice with myocardial ischemia could be exerted at least in part by regulating the NF-κB signaling pathway. Graphical abstract: Image 1 Highlights: The mechanisms of DLT in treating AWMI are unknown. We investigate the effect of DLT on AWMI and the underlying mechanisms. We used the ApoE −/- mice fed a high fat feed combined with ISO injection to establish the animal model of AWMI. We indicate that the inhibitory effect of DLT on MMP-1 and MMP-2 might be one of the mechanisms by which it prevents AWMI. We found that the administration of DLT is effective for treating atherosclerosis, myocardial ischemia, or AWMI in mice. The therapeutic efficacy of DLT in the HG, IG and HIG groups could be regulated by the NF-κB signaling pathway.